2019
DOI: 10.1002/bab.1816
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme production and oil palm empty fruit bunch bioconversion to ethanol using a hybrid yeast strain

Abstract: Oil palm empty fruit bunch (OPEFB) is a lignocellulosic biomass generated in palm oil mills. It is a sustainable resource for fuels and chemicals. In this study, OPEFB was converted to ethanol by an integrative OPEFB conversion process including dilute alkaline pretreatment, cellulolytic enzyme production, separate OPEFB hydrolysis, and cofermentation using a hybrid xylose-fermenting yeast. OPEFB was pretreated using 1% (w/v) NaOH solution followed by 1% (v/v) H 2 O 2. Further, cellulolytic enzymes were produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Proses persiapan yang efektif sangat d i b u t u h k a n u n t u k m e m p e r c e p a t p r o s e s pengomposan untuk mencapai kualitas kompos TKKS yang diharapkan (Hamzah et al, 2018;Himmatun Wisda et al, 2016;Zulkiple et al, 2016). Persiapan TKKS dapat dilakukan dengan metode fisika, kimia, fisika-kimia, maupun biologis (Anita et al, 2020;Hamzah et al, 2018;Hidayat, 2013;Isroi et al, 2012;Muhd Ali et al, 2016;Zahrim et al, 2017;Zhai et al, 2020 Dalam proses pengomposan, diperlukan metode untuk menurunkan rasio C/N untuk meningkatkan kandungan nutrisi yang dapat diserap oleh tanaman. Tingginya rasio C/N disebabkan oleh tingginya kandungan C-organik yang diakibatkan oleh tingginya kandungan gula kompleks (Tahir et al, 2019).…”
Section: A Persiapan Substrat Tkksunclassified
“…Proses persiapan yang efektif sangat d i b u t u h k a n u n t u k m e m p e r c e p a t p r o s e s pengomposan untuk mencapai kualitas kompos TKKS yang diharapkan (Hamzah et al, 2018;Himmatun Wisda et al, 2016;Zulkiple et al, 2016). Persiapan TKKS dapat dilakukan dengan metode fisika, kimia, fisika-kimia, maupun biologis (Anita et al, 2020;Hamzah et al, 2018;Hidayat, 2013;Isroi et al, 2012;Muhd Ali et al, 2016;Zahrim et al, 2017;Zhai et al, 2020 Dalam proses pengomposan, diperlukan metode untuk menurunkan rasio C/N untuk meningkatkan kandungan nutrisi yang dapat diserap oleh tanaman. Tingginya rasio C/N disebabkan oleh tingginya kandungan C-organik yang diakibatkan oleh tingginya kandungan gula kompleks (Tahir et al, 2019).…”
Section: A Persiapan Substrat Tkksunclassified
“…Zhai et al. [1] demonstrate the feasibility of an innovative integrative process that includes dilute alkaline pretreatment, cellulolytic enzyme production, OPEFB hydrolysis, and cofermentation with a hybrid xylose‐fermenting yeast. Their work opens new perspectives for the use of OPEFB biomass to produce ethanol.…”
Section: Innovative Processes For the Production Of Bioethanol Butanmentioning
confidence: 99%
“…Enzyme synthesis can be accomplished through fermentation by microbial organisms, often bacteria or fungi [12]. It has been shown that fungi exhibit a greater hydrolysis rate in comparison to yeast and bacteria.…”
Section: Introductionmentioning
confidence: 99%